Projeto datacenter pequeno porte - Escouto, Fabiano Lopes (Universidade do Vale do Rio dos Sinos, 2016)
This monograph presents a project plan and its subsidiary plans using the best project management practices established by PMI (Project Management Institute) to implement a small Datacenter. All stages of the project and the processes used to develop them are specified in this paper.
Keywords: Projeto; Processos; Escopo; Requisitos; Custos; Qualidade; Gerente; Patrocinador; Stakeholders